Development of a Model of the Mechanism of Saturation with Small Impurity Particles of Raw Cotton During Movement in the Pneumatic Conveying System of Cotton Harvesting Machines (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article analyzes the contamination of machine-picked raw cotton. It focuses on how small particles of impurities saturate raw cotton during transportation within the pneumatic conveying system of a cotton harvester. A model was developed to understand how these small impurity particles approach the clusters of raw cotton as they move from the receiving chamber to the harvester's hopper. Using the MathCAD-15 programming environment, we created graphs based on this model. Additionally, another model was constructed to illustrate how small particles penetrate the fiber strands. Numerical calculations conducted with the developed model revealed that an increase in the concentration and mass of these small impurity particles leads to a deeper penetration into the fiber strands. The results from these numerical studies confirmed the reliability of the experimental findings. Based on the analysis, we provide recommendations to reduce the contamination of raw cotton in the hopper.